Diffusion photocurrent influenced by intraband excitation in an intermediate band solar cell with type-I band alignment. (1st July 2022) - Zhu, Yaxing; Asahi, Shigeo; Miyashita, Naoya; Okada, Yoshitaka; Kita, Takashi
Abstract: We elucidate a photocarrier collection mechanism in intermediate band solar cells (IBSCs) with InAs-quantum dots (QDs)-in-an-Al0.3 Ga0.7 As/GaAs-quantum well structures. When the Al0.3 Ga0.7 As barrier is excited, the device electrical output can be varied by additional infrared light for the electron intraband optical transition in QDs. The photocurrent in IBSC with a single QDs-in-a-well structure shows a monotonic increase with the intraband-excitation density. Conversely, IBSC with a multilayered QDs-in-a-well structure exhibits a photocurrent reduction when electrons in QDs are optically pumped out. The simultaneously measured photoluminescence spectra proved that the polarity of QD states changes depending on the intraband-excitation density. We discuss the drift and diffusion current components and point out that the hole diffusion current is significantly influenced by carriers inside the confinement structure. Under strong intraband excitations, we consider an increased hole diffusion current occurs by blocking hole-capture in the quantum structures. This causes unexpected photocurrent reduction in the multilayered device.